Comparative Study of Feeding and Nutrition for Beef Cattle in Smallholder Farmers: Case Study in Regencies of Malang, Pamekasan, and Tuban: Comparative Study of Feeding and Nutrition for Beef Cattle in Smallholder Farmers: Case Study in Regencies of Malang, Pamekasan, and Tuban - Asri Nurul Huda; Kusmartono; Poespitasari Hazanah Ndaru; Trinil Susilawati; Mashudi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
This study evaluated feeds for fattening and breeding beef cattle in smallholder farmers located in Malang, Pamekasan, and Tuban regencies. The research was conducted using two methods i.e., survey and laboratory analysis. The data survey was carried out in each area, and 30 respondents (n=30) were observed per area in classification of low to medium livestock ownership. Laboratory analysis was performed to analyse the chemical composition of the feed and to measure the total gas production. The data analysis approach used quantitative descriptive to describe the nutritional value quality of beef cattle feed with available quantitative data. The results showed variations in the nutrient content of the beef cattle feed in three different study locations in smallholder farmers located in Regency of Malang, Pamekasan, and Tuban while the total gas production showed a high production in the fattening cattle feeds between three study locations. Thus, it was concluded that the feed for fattening cattle had better nutrient content in terms of crude protein content and total gas production than the breeding cattle feed. Key words: cattle feed, nutrition, gas production